Analysis of Clinical Success in HIV/AIDS Patients with First-Line Antiretroviral Therapy - Devientasari, Chinthia; Putri, Luluk Aniqoh Meliana (Open Access Health Scientific Journal, 2025)
Background: Clinical success in HIV/AIDS patients undergoing antiretroviral therapy (ART) is influenced by various factors, including treatment adherence, regular follow-up visits, and monitoring of clinical outcomes such as weight gain and the absence of opportunistic infections (OIs). Opportunistic infections are considered a key indicator of ART failure and are strongly associated with advanced disease stages and low CD4 counts. This study aimed to analyze the demographic and clinical characteristics of HIV/AIDS patients and evaluate the relationship between body weight and the incidence of opportunistic infections in patients receiving ART.Methods: This cross-sectional study used retrospective data from 95 HIV/AIDS patients collected through consecutive sampling. Data included demographic variables (gender, age, marital status, education, occupation), clinical stage (WHO), CD4 count, body weight, ART regimen, and opportunistic infections. Data were analyzed using the Chi-square test, with a p-value ≤0.05 considered statistically significant.Results: Most patients were male (52.6%) and in the productive age range of 25–46 years (74.7%). The majority were married (54.7%), had low educational attainment, and were employed (76.8%). Clinically, 88.4% were at WHO stage III, and 80% had CD4 counts <350 cells/mm³. Low body weight (<60 kg) was found in 93.7% of patients. Opportunistic infections occurred in 26.3% of patients. A statistically significant association was found between body weight and opportunistic infections (p = 0.041). However, the OR of 1.086 (95% CI: 0.479–2.464) indicated no clinically significant difference in the risk of opportunistic infections between patients with body weight <60 kg and those >60 kg.Conclusion: Although low body weight was statistically associated with opportunistic infections, it did not present a significantly increased clinical risk. Nonetheless, opportunistic infections among patients highlights the importance of early intervention, nutritional support, and timely initiation of ART to improve treatment outcomes in HIV/AIDS management.